Editorial: ONO‐2952 in irritable bowel syndrome with diarrhoea – authors' reply. Issue 7 (3rd March 2017) - Whitehead, W. E.; Duffy, K.; Sharpe, J.; Nabata, T.; Bruce, M.
Abstract : Linked Content This article should be linked to Nee and Lembo, and W. E. Whitehead et al papers. To view these articles visithttps://doi.org/10.1111/apt.13920 andhttps://doi.org/10.1111/apt.13839 .